TEPUNG PUPA-MULBERRY (PURY) SEBAGAI BAHAN PANGAN ALTERNATIF KAYA GIZI - Trina Astuti; Clara Meliyanti Kusharto (Jurnal Gizi dan Pangan, 2009)
Silkworm pupae is immature stage of moth.  It is inner part of the silkworm cocoon shell which usually disposed from yarn silk production, and now has become a valuable ingredient of human food in many countries, however it is not common yet in Indonesia. The purpose of study is to develop a weaning food as nutritious basic formula of complementary food from pupae waste. A silkworm pupae was a major constituents used as materials. There are sixth  steps to get PURY properly: select a fresh, fine and clean pupae, steamed well about 10 seconds, grinded and sifted it  to get liquid, added 10% maize powder, dried in oven at 60ºC for 6 hours, and refine on blender. A fine powder, so called “PURY”, has a well balanced amount of moisture, protein, fat included PUFA, carbohydrate, amino acids, vitamins and minerals. Through a simple processing, the dry product of fine PURY powder can be obtained and used as a basic formula of complementary food and snacks and has made great contribution to reduce pupae waste. Research is continued to scale up producing PURY based product for more food-technological uses in order to reduce prevalence of malnutrition in Indonesia.